Spontaneous endometriosis in cynomolgus monkeys as a clinically relevant experimental model. Issue 7 (19th April 2018) - Nishimoto-Kakiuchi, A; Netsu, S; Okabayashi, S; Taniguchi, K; Tanimura, H; Kato, A; Suzuki, M; Sankai, T; Konno, R
Abstract: STUDY QUESTION: Does spontaneous endometriosis in cynomolgus monkeys have the characteristics required of a good experimental model? SUMMARY ANSWER: Spontaneous endometriosis in cynomolgus monkeys exhibited similar clinicopathological characteristics to the human disease and was useful as an experimental model. WHAT IS KNOWN ALREADY: The prevalence of endometriosis in autopsied cynomolgus monkeys ( Macaca fascicularis ) in a breeding colony was reported to be 28.7% in 1993. The histopathological findings we reported recently showed that components of spontaneous endometriosis were not only endometriotic epithelium and stromal cells (CD10-positive) with hemorrhage and inflammation, but also smooth muscle metaplasia and nerve fibers. STUDY DESIGN, SIZE, DURATION: During routine medical examinations at a research facility from 2008 to 2012, 614 female cynomolgus monkeys of reproductive age (6–25 years) were screened for endometriosis by the presence of regular menstrual bleeding, serum CA125 levels and palpation of the abdomen. In total, 29 monkeys were selected as subjects for the following study. PARTICIPANTS/MATERIALS, SETTING, METHODS: Of the 29 monkeys selected, 15 were diagnosed with endometriosis by laparoscopy and/or open surgery. The monkeys were monitored by observing their general condition, and eight of these were monitored using laparoscopy and MRI. In addition, to investigate appropriate screening parameters and endometriosis-associated biological parameters in monkeys, we retrospectively examined general laboratory parameters that correlate to the menstrual cycle and disease status. MAIN RESULTS AND THE ROLE OF CHANCE: The combination of CA125 serum levels (this was a useful marker for chocolate cysts), palpation of the abdomen, and fecal abnormalities was the most efficient screening method for diagnosing monkeys with endometriosis. Each animal could be diagnosed and assigned a disease stage by laparoscopy. While monitoring the disease stage by laparoscopy and/or MRI, disease status in individual monkeys was mainly stable or was progressive for 2–7 months. The detection rate by screening was low (15/614) but age-specific analysis suggests that screening would be more efficient if a colony for an endometriosis model is maintained with 11–20-year olds. As an endometriosis-associated biological parameter, the decrease in food consumption that coincided with menstruation was selected and correlated well ( R 2 value = 0.8239) with disease status (according to a modified adhesion revised American Fertility Society score). LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Peritoneal fluid was not analyzed because a smaller amount is produced in cynomolgus monkeys than in baboons. Although clinical endometriosis-associated pain is evaluated in women using a visual analog scale, pain could not be directly evaluated in this non-human primate model. WIDER IMPLICATIONS OF THE FINDINGS: Although cynomolgus monkeys are relatively small (2–5 kg) primates, laparoscopy and MRI make it possible to evaluate spontaneous endometriosis in these monkeys and to monitor its development over time. Spontaneous endometriosis in cynomolgus monkeys is a useful model for evaluating disease progress and drug efficacy because they have similar lesions to those in humans, and conventional laboratory methods and parameters for assessment are well established. STUDY FUNDING/COMPETING INTEREST(S): No external funds were used for this study. A.N.-K., K.T., H.T., A.K. and M.S. are full-time employees of Chugai Pharmaceutical Co., Ltd. R.K. received a consultancy fee from Chugai Pharmaceutical Co., Ltd. and lecture fees from Chugai Pharmaceuticals, Japan Vaccine Co. Ltd., Merck & Co., Mochida Co. Ltd., Roche Diagnostics, and BD, unrelated to the submitted work. S.N., S.O. and T.S. have nothing to declare.